119k views
1 vote
You don't have to show work
4+(2x−7)3=−5 ?

User Rogerio
by
5.3k points

2 Answers

6 votes

Answer: x = 2.

Step-by-step explanation: Step 1: Simplify both sides of the equation.

4+(2x−7)(3)=−5

4+(2x)(3)+(−7)(3)=−5(Distribute)

4+6x+−21=−5

(6x)+(4+−21)=−5(Combine Like Terms)

6x+−17=−5

6x−17=−5

Step 2: Add 17 to both sides.

6x−17+17=−5+17

6x=12

Step 3: Divide both sides by 6.

6x /6 = 12 /6

x = 2.

User NotGeek
by
5.0k points
5 votes
it would be -3x+2x if you were talking about the whole question like 4+(2x-7)3=-5 it would be x=2
User Gangnus
by
5.1k points